(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
In this article, the author presents thirteen theses on the impact that artificial intelligence has and can have on a social and legal level. Starting with a description of the characters of cybersociety, he considers the potentialities and risks of the future use of AI, dealing with fundamental rights and balances of powers.